2011
DOI: 10.1007/s11739-011-0636-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute exacerbations on circulating endothelial, clotting and fibrinolytic markers in COPD patients

Abstract: Patients with chronic obstructive pulmonary disease (COPD) are prone to clinical exacerbations that are associated with increased airway inflammation, a potent pro-thrombotic stimulus. Limited information is available on the mechanisms underlying the putative alterations of the endothelial-coagulative system during acute exacerbations. The aim was to investigate whether the activation of the endothelial-coagulative system occurs in association with the acute inflammatory response of COPD exacerbation. We monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 33 publications
3
37
0
2
Order By: Relevance
“…It showed a moderate reproducibility as shown in figure 1 I. Confounder analysis revealed that higher serum vWF levels in COPD patients could not be explained by changed covariates (FEV1 or pack-years, ANCOVA p-values for all confounders <0.01) and no significant association between smoking and vWF levels was found in the ARIC study [24]. Two reports that found vWF to be significantly increased in COPD patients with acute exacerbations [25] [26] support the potential clinical value of this blood marker.…”
Section: Discussionmentioning
confidence: 86%
“…It showed a moderate reproducibility as shown in figure 1 I. Confounder analysis revealed that higher serum vWF levels in COPD patients could not be explained by changed covariates (FEV1 or pack-years, ANCOVA p-values for all confounders <0.01) and no significant association between smoking and vWF levels was found in the ARIC study [24]. Two reports that found vWF to be significantly increased in COPD patients with acute exacerbations [25] [26] support the potential clinical value of this blood marker.…”
Section: Discussionmentioning
confidence: 86%
“…In addi-tion, E-selectin EMPs were released from both aortic ECs and pulmonary microvascular ECs, although they were not released by H 2 O 2 and CSE stimulation. E-selectin has previously been reported to be upregulated when endothelial cells were activated, and endothelial activation was reported to be induced during COPD exacerbation [28,29]. We have previously shown that circulating E-selectin EMPs were released during exacerbation [3].…”
Section: Experimental Lung Researchmentioning
confidence: 77%
“…Elevated levels of von Willebrand factor, D-dimer, and prothrombin fragment 1ϩ2, being surrogate markers for inflammation, endothelial damage, and clotting activation, respectively, have been measured during an exacerbation of COPD. 19 A number of studies have demonstrated that subjects with COPD have an increased platelet count and also increased platelet ac- CRP ϭ C-reactive protein WBC ϭ white blood cell MPV ϭ mean platelet volume tivation in stable disease and further in the exacerbation period. 8,20 However, this platelet activation can follow different patterns as to mean platelet volume values in various diseases.…”
Section: Discussionmentioning
confidence: 99%